Essays on human capital formation in developing countries - Singh, A (2014)
This thesis consists of a short introduction and three self-contained analytical chapters. Chapter 1 focuses on the question of learning gaps and divergence in achievement across countries. I use unique child-level panel data from Ethiopia, India, Peru and Vietnam to ask at what ages do gaps between different populations emerge, how they increase or decline over time, and what the proximate determinants of this divergence are. I document that learning gaps between the four countries are already evident at the age of 5 years and grow throughout the age trajectory of children, preserving country ranks from 5 to 15 years of age. At primary school age, the divergence between Vietnam and the other countries is largely accounted for by substantially greater learning gains per year of schooling. Chapter 2 focuses on learning differences between private and government school students in India. I present the first value-added models of learning production in private and government schools in this context, using panel data from Andhra Pradesh. I examine the heterogeneity in private school value-added across different subjects, urban and rural areas, medium of instruction, and across age groups. Further, I also estimate private school effects on children's self-efficacy and agency. I find modest or insignificant causal effects of attending private schools in most test domains other than English and on children's academic self-concept and agency. Results on comparable test domains and age groups correspond closely with, and further extend, estimates from a parallel experimental evaluation. Chapter 3 uses panel data from the state of Andhra Pradesh in India to estimate the impact of the introduction of a national midday meal program on anthropometric z-scores of primary school students, and investigates whether the program ameliorated the deterioration of health in young children caused by a severe drought. Correcting for self-selection into the program using a non-linearity in how age affects the probability of enrollment, we find that the program acted as a safety net for children, providing large and significant health gains for children whose families suffered from drought.